Development of an colloidal gold immunochromatography assay strip for the diagnosis of Babesia canis - Wang, Jianzhong; Liu, Jing; Zhang, Siyuan; Zhou, Rui; Qiu, Jicheng; Zhao, Yi; Ma, Xianglin; Wu, Xiaojie; Li, Xiaoguang; Mao, Wei; Liu, Yiduo (Frontiers in Veterinary Science, 2025)
IntroductionCanine babesiosis, caused by Babesia canis, is a tick-borne hemolytic disease requiring rapid, reliable diagnostic tools to protect canine health in resource-limited settings.MethodsWe developed a colloidal gold immunochromatographic assay (CGIA) strip using a recombinant BcMSA1-BcSA1 fusion protein, expressed in Escherichia coli with a yield of 2.5 mg/L, combining hydrophilic domains of merozoite surface antigen (BcMSA1) and secreted antigen (BcSA1). Seventy-two serum samples from veterinary clinics in Shanxi Province, China (ethical approval SXAU-2022-013), were tested against a commercial ELISA kit (Anigen Rapid B. canis Ab Test Kit), with infections confirmed by microscopy and PCR. Specificity was assessed using sera positive for Theileria spp., Toxoplasma gondii, Ancylostoma caninum, Eimeria canis, Canine distemper virus, and Canine parvovirus.ResultsThe CGIA strip showed no cross-reactivity, a detection limit of 1:8 for B. canis-positive sera, and retained efficacy after 18 months at room temperature. Sensitivity was 84%, specificity 93.6%, and Cohen’s Kappa was 0.935 compared to ELISA.DiscussionThis stable, user-friendly CGIA strip offers an efficient point-of-care solution for B. canis detection, overcoming limitations of traditional methods and supporting epidemiological and clinical applications.